ABOUT THE SECOND INTERNATIONAL FLOWER BREEDING TRADE EXHIBITION - N. S. Tsiganok; G. D. Levko (Овощи России, 2012)
September 5-7, 2012 in the arcade of Moscow there was the second exhibition devoted to floriculture Russia «Expo Flora Russia».